Preparation and pharmacological characterization of the enantiomers of the anticancer agent R/S-N-3-cyanophenyl-N'-(6-tert-butoxycarbonylamino-3,4-dihydro-2,2-dimethyl-2H-1-benzopyran-4-yl)urea: Identification of the R-enantiomer as the active eutomer - Michael Schnekenburger; Eric Goffin; Matthieu Schoumacher; Nikolay Tumanov; Ange Mouithys-Mickalad; Pascal de Tullio; Johan Wouters; Philippe Lebrun; Marc Diederich; Bernard Pirotte (European Journal of Medicinal Chemistry Reports, 2025)
R/S-N-3-cyanophenyl-N'-(6-tert-butoxycarbonylamino-3,4-dihydro-2,2-dimethyl-2H-1-benzopyran-4-yl)urea (BPDZ 711, 4) initially designed as a KATP channel opener, was found to exhibit diverse biological activities. The compound inhibited insulin release from rat pancreatic islets, indicating a potential effect on glucose metabolism. Oxygraphy measurements on chronic myeloid leukemia (CML) K-562 cells revealed an impact on cellular respiration. Additionally, the compound demonstrated inhibitory activity on histone deacetylase class III enzymes (sirtuins), linking metabolic and epigenetic regulation. This was corroborated by its effect on protein acetylation and modulation of the extracellular pH of treated CML cells. Alterations in CML cells' nuclear morphology and the release of high-mobility group box 1 (HMGB1) protein confirmed mechanisms related to cellular stress and immunogenic cell death. BPDZ 711 preserved the viability of peripheral blood mononuclear cells, thus demonstrating excellent differential toxicity.Since BPDZ 711 is a racemate, the present study focused on the preparation of the two enantiomers and examined the possibility that each isomer could display a distinct pharmacological profile. Our data revealed that the R-enantiomer (5) of BPDZ 711 was consistently the most biologically active compound (eutomer), making it the reference compound for future drug discovery and development.